Preparation method of water treatment coagulant compounding inorganic high-molecular polymer and adsorption material

By combining PATC with MgCl2 modified multi-wall carbon nanotubes to generate bimetallic oxides, the problem of poor removal of small molecule organic matter in the prior art is solved, and the efficient removal of organic matter in water is achieved, and the operation is simple and suitable for practical applications.

CN119822469AActive Publication Date: 2025-04-15HENGLI PETROCHEMICAL (DALIAN) REFINING & CHEM CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411939575.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-15
Estimated Expiration
2044-12-26

Smart Images

  • Figure HDA0005212292710000011
    Figure HDA0005212292710000011
  • Figure HDA0005212292710000012
    Figure HDA0005212292710000012
Patent Text Reader

Abstract

The invention discloses a preparation method of a water treatment coagulant compounding an inorganic high-molecular polymer and an adsorption material, and relates to the field of water treatment. The coagulant is formed by compounding an inorganic polymeric coagulant PATC and an adsorption material multi-walled carbon nanotube, and the multi-walled carbon nanotube is a multi-walled carbon nanotube modified by MgCl2. The water treatment coagulant is mainly applied to removal of natural organic matters in a water body and has an obvious effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of water treatment, and in particular to a method for preparing a water treatment coagulant of a composite inorganic macromolecular polymer and an adsorption material. Background Art

[0002] After the water body is treated at the front end in the drinking water plant, it will be disinfected at the back end, and the disinfectant will react with the natural organic matter remaining in the water to generate disinfection by-products. Disinfection by-products have the three effects of "teratogenicity, carcinogenicity, and mutagenicity" on human health, so it is inevitable to reduce the formation of disinfection by-products. Considering the economic cost, operational convenience, and feasibility, it is the preferred solution for the precursor of disinfection by-products, natural organic matter, to remove the content. The methods for removing natural organic matter from water bodies mainly include enhanced coagulation, adsorption, membrane separation, ion exchange, ozone oxidation, etc. Among them, the enhanced coagulation method can non-selectively remove natural organic matter from water bodies, and it is widely used in water treatment due to its large water treatment volume, simple operation, and low cost.

[0003] Conventional coagulants are mainly divided into inorganic coagulants and organic coagulants, among which inorganic coagulants are mainly metal salt coagulants, such as iron salt coagulants, aluminum salt coagulants, and titanium salt coagulants. At present, polyaluminum chloride (PAC) is favored by many water plants due to its superior coagulation effect; in addition, polyferric chloride (PFC), polyferric sulfate (PFS), polytitanium chloride (PTC), etc. have been developed and applied in water treatment. On the basis of polymerized inorganic polymer coagulants, bimetallic polymer coagulants such as polyaluminum ferric chloride are prepared in the form of bimetallic. Due to its bimetallic form, it has a strong positive charge and can combine with negatively charged natural organic matter in the water body according to the principle of electrical neutralization. In addition, these metal coagulants undergo hydrolysis reactions in water to generate metal hydroxides, which can remove organic matter in water through adsorption bridging and net capture and sweeping mechanisms. Polyaluminum-titanium chloride bimetallic coagulant has improved charge neutralization ability due to the introduction of tetravalent titanium. Studies have shown that PATC has a better ability to remove large molecular organic matter in water, but the removal of small molecular organic matter needs to be improved. Summary of the invention

[0004] In view of the advantages of PATC and existing problems, the purpose of the present invention is to provide a method for preparing a water treatment coagulant of a composite inorganic high molecular polymer and an adsorbent material.

[0005] In order to meet the above-mentioned purpose, the preparation method of the present invention is as follows:

[0006] The invention discloses a method for preparing a water treatment coagulant composited with inorganic high molecular polymer and adsorbent material. The coagulant is composited with inorganic polymer coagulant PATC and adsorbent material multi-walled carbon nanotubes (MWCNTs), and the multi-walled carbon nanotubes are multi-walled carbon nanotubes modified with MgCl2.

[0007] Furthermore, the inorganic polymer coagulant PATC and the multi-walled carbon nanotubes modified with MgCl2 are mixed by oscillation.

[0008] Furthermore, the mass ratio of the multi-walled carbon nanotubes in the multi-walled carbon nanotubes modified by MgCl2 to Al in the inorganic polymer coagulant PATC is 10-50%, for example, 10%, 30%, or 50%.

[0009] Furthermore, the time for ultrasonic mixing of the inorganic polymer coagulant PATC and the multi-walled carbon nanotubes modified with MgCl2 is 0.5-2 hours, for example, 0.5, 1.0, or 2.0 hours.

[0010] Furthermore, the inorganic polymer coagulant PATC is prepared by reacting AlCl3 and TiCl4 in an ice-water bath.

[0011] Furthermore, the molar ratio of Al in the AlCl3 to Ti in the TiCl4 is 10-30:1, for example, 10:1, 15:1, 20:1, 30:1.

[0012] Furthermore, the AlCl3 is a 0.05-1.0 mol / L AlCl3 solution, the TiCl4 is a 98% TiCl4 solution, and the reaction time is 2-5 h; specifically, the 0.05-1.0 mol / L AlCl3 solution and the 98% TiCl4 solution are mixed and reacted in an ice-water bath for 2-5 h, and the reaction is carried out under stirring conditions at a stirring speed of 200-300 r / min.

[0013] Furthermore, TiCl4 needs to be added slowly, and the dropping speed of the TiCl4 solution is 0.1-1 mL / min.

[0014] Further, the reaction solution of AlCl3 and TiCl4 is treated with Na2CO3 to adjust the basicity (B = C(OH-) / C(Al 3+ +Ti 4+ )) to 1.5-1.8, for example, 1.5, 1.6, 1.7, 1.8; then, stirring at a speed of 200-300 r / min for 2-5 hours, standing and maturing for 12-24 hours, to obtain a PATC solution.

[0015] Furthermore, the Na2CO3 is a 0.5-1.0 mol / L Na2CO3 solution, and the dropping speed of the Na2CO3 solution is 0.1-1 mL / min.

[0016] Furthermore, the MgCl2-modified multi-walled carbon nanotubes are formed by mixing multi-walled carbon nanotubes with MgCl2 by oscillation and then pyrolyzing them at a high temperature of 150-400°C (e.g., 150, 300, 350, 400°C) for 2-5 hours (e.g., 2, 3, 4, 5 hours).

[0017] Furthermore, the ratio of the multi-walled carbon nanotubes to MgCl2 is 1g:1-10mmol, preferably 1-5mmol; for example, 1g:1mmol, or 1g:3mmol, 1g:5mmol.

[0018] Furthermore, the multi-walled carbon nanotubes are soaked in anhydrous ethanol to remove impurities, and then dried for standby use.

[0019] Furthermore, the multi-walled carbon nanotubes and MgCl2 are oscillated for 12-24 hours, such as 12, 16, 20, or 24 hours; and the rotation speed of the oscillation is 200-300 r / min.

[0020] Specifically, the preparation method of the water treatment coagulant comprises the following steps:

[0021] (1) Prepare 0.05-1 mol / L AlCl3 solution, add TiCl4 in an ice-water bath to make the Al / Ti ratio (n / n).

[0022] (2) After the above solution is stirred at a speed of 200-300 r / min for 5-20 min, 0.5-1.0 mol / L Na2CO3 solution is slowly added to adjust the alkalinity of the solution to 1.5, 1.6, 1.7, or 1.8.

[0023] (3) After the above solution is prepared, it needs to be stirred at a speed of 200-300 r / min for 2-5 hours, and then left to mature at room temperature for 12-24 hours to obtain a PATC solution of a certain concentration.

[0024] (4) The multi-walled carbon nanotubes are soaked in anhydrous ethanol to remove impurities, and then dried for later use.

[0025] (5) Multi-walled carbon nanotubes and MgCl2 are oscillated in a ratio of 1 g:1-10 mmol, dried at a constant temperature, pyrolyzed at 150-400°C for 2-5 hours, and then ground for use to obtain MgCl2-modified multi-walled carbon nanotubes.

[0026] (6) The multi-walled carbon nanotubes in the multi-walled carbon nanotubes modified by MgCl2 and the Al in the PATC solution are ultrasonically mixed in a mass ratio of 10%-50%, and the ultrasonic mixing time is 0.5-2 hours. The application of the above-mentioned water treatment coagulant in water treatment is mainly used to remove natural organic matter in water bodies.

[0027] The composite coagulant of PATC composite modified multi-walled carbon nanotubes has the following advantages in water treatment:

[0028] 1. The present invention utilizes the effective ingredients (Al-O-Ti) and strong charge characteristics of the bimetallic polymer coagulant to combine with the multi-walled carbon nanotubes modified with metals. When the multi-walled carbon nanotubes are subjected to ultrasonic reaction with PATC, the effective ingredients in PATC react with the metal compounds on the surface of the multi-walled carbon nanotubes to generate covalent bonds of three bimetallic oxides of Al-O-Mg, Al-O-Ti, and Mg-O-Ti, which can effectively enhance the ability to remove organic matter.

[0029] 2. This method uses actual water bodies for experiments. When the dosage is 0.20mmol / L, the DOC removal rate reaches more than 60%; the residual aluminum content is less than 0.2mg / L.

[0030] 3. The operation method of the present invention is simple, the DOC removal rate effect is obvious, the coagulation effect is enhanced, the preparation method is simple, and it can be applied in practice. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a comparison chart of the DOC removal rates of different composite coagulants prepared in Examples 1-3 of the present invention at different dosages for actual water bodies;

[0032] Figure 2 The composite coagulant prepared in Example 2 of the present invention at different dosages for the UV of actual water bodies 254 , and the comparison chart of the removal of residual aluminum. DETAILED DESCRIPTION

[0033] In order to further understand the purpose, technical solutions and advantages of the present invention, the technical solutions of the present invention will be further described below, and the present invention will be explained in detail with examples and drawings.

[0034] Unless otherwise specified, the medicines involved in the following embodiments are all commonly available commodities.

[0035] Unless otherwise specified, the experimental methods used in the following examples are conventional experimental methods.

[0036] The invention provides a coagulant combining the dual effects of coagulation and adsorption, which has good performance in removing organic matter. Polyaluminium titanium chloride is prepared by ice-water bath, and is compounded with modified multi-walled carbon nanotubes under oscillating ultrasonic conditions. While PATC hydrolyzes and removes macromolecular organic matter, the abundant metal functional groups on the surface of the multi-walled carbon nanotubes adsorb negatively charged organic matter, thereby improving the removal efficiency of organic matter in the coagulation process and shortening the adsorption reaction time.

[0037] Example 1

[0038] This example is used to illustrate a method for preparing a water treatment coagulant of a composite inorganic high molecular polymer and an adsorbent material. The specific steps of the preparation method are as follows:

[0039] (1) Prepare 0.1 mol / L AlCl3 solution, and add 98% TiCl4 solution dropwise in an ice-water bath to make the Al / Ti ratio 15:1 (n / n).

[0040] (2) After stirring the above solution at 300 r / min for 5-10 min, 1.0 mol / L Na2CO3 solution was slowly added drop by drop to adjust the alkalinity of the solution to 1.5.

[0041] (3) After the above solution is prepared, it needs to be stirred at a speed of 300 r / min for 4 hours and then left to mature for 24 hours to obtain a PATC solution of a certain concentration.

[0042] (4) Weigh 1 g of multi-walled carbon nanotubes and add them to 1 L of 5 mmol / L MgCl2 solution, shake at room temperature for 24 h, centrifuge to obtain the solid, dry at 60°C for 12 h, and then pyrolyze in a muffle furnace at 350°C for 2 hours to obtain MgCl2-modified multi-walled carbon nanotubes, which are ground and set aside.

[0043] (5) Weigh 100 mL of PATC solution, add MgCl2-modified multi-walled carbon nanotubes thereto, mix the modified multi-walled carbon nanotubes and PATC in a ratio of MWCNTs / Al=10%, and ultrasonicate for 30 min to obtain a composite coagulant, recorded as PATC@TMgMW-10%.

[0044] Example 2

[0045] The difference between this embodiment and embodiment 1 is that in step (5), the ratio of multi-walled carbon nanotubes to PATC is MWCNTs / Al=30%, and the mixture is ultrasonicated for 30 minutes, and the obtained composite coagulant is PATC@TMgMW-30%.

[0046] Example 3

[0047] The difference between this embodiment and embodiment 1 is that in step (5), the ratio of multi-walled carbon nanotubes to PATC is MWCNTs / Al=50%, and the mixture is ultrasonicated for 30 minutes, and the obtained composite coagulant is PATC@TMgMW-50%.

[0048] Example 4

[0049] In order to investigate the effects of different composite coagulants on organic matter in water at different contents, the composite coagulants prepared in Examples 1-3 were selected under the conditions of 0.12mmol / L and 0.20mmol / L, respectively, to investigate the effects of different composite coagulants on organic matter in water; the composite coagulants prepared in Example 2 were selected under the conditions of 0.02mmol / L, 0.04mmol / L, 0.08mmol / L, 0.12mmol / L, 0.16mmol / L, and 0.20mmol / L, respectively, to investigate the effects of composite coagulants on organic matter in water at different contents, and no composite coagulant was added as a comparison; the water body was selected with DOC of 56.5mg / L and UV 254 =0.078 of the actual water body.

[0050] A six-joint agitator was used for the coagulation experiment.

[0051] Take 500ml of water sample and put it into a beaker. Add the composite coagulant during rapid stirring (speed 250rpm), stir for 2min, then stir slowly (speed 40rpm) for 10min to promote the formation of flocs. Finally, let it settle for 30min to allow the flocs to settle to the bottom of the beaker, and take the supernatant for measurement data.

[0052] After the coagulation experiment, the results of removing DCOC in water by different coagulants are shown in Figure 1 . The experimental results used two dosages to compare the DOC removal of different coagulants. At the same dosage, with the increase of multi-walled carbon nanotubes, there will be a trend of first rising and then falling. The reason for this is that the appropriate amount of multi-walled carbon nanotubes can effectively react with the main components in PATC, enhance their own adsorption capacity, and do not damage the coagulation efficiency of PATC itself, which promotes the improvement of the coagulation effect of the composite coagulant. However, the addition of excessive multi-walled carbon nanotubes will react with the main components of PATC in large quantities, reducing the effective ingredients in PATC. The coagulation efficiency itself is reduced, resulting in a worse coagulation effect. Increasing the dosage of the composite coagulant, due to the high DOC content of the raw water, appropriately increasing the dosage of the coagulant can improve the coagulation effect.

[0053] Select PATC@TMgMW-30% UV at different dosages 254 The experimental results are shown in Figure 2 .UV254 It steadily decreases with the increase of dosage. UV254 can be used as an indicator of the content of hydrophobic organic matter in water. 254 The reduction of the content of residual aluminum in water has proved the ability of the composite coagulant to remove hydrophobic organic matter. The main body of the composite coagulant selected is a polymer coagulant with Al and Ti bimetallic, and the Al content accounts for 85%, so it is necessary to investigate the residual aluminum content in the water. From the analysis of the results, with the increase of the dosage, the residual aluminum content will have a trend of first rising and then falling, and finally stabilize at 40μg / L, which is far lower than the national standard requirement of 0.2mg / L, reducing the threat to human health.

[0054] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a water treatment coagulant of a composite inorganic high molecular polymer and an adsorbent material, characterized in that: The coagulant is composited by an inorganic polymer coagulant PATC and an adsorption material multi-walled carbon nanotube, and the multi-walled carbon nanotube is a multi-walled carbon nanotube modified by MgCl2.

2. The preparation method according to claim 1, characterized in that: The inorganic polymer coagulant PATC and the multi-walled carbon nanotubes modified by MgCl2 are ultrasonically mixed, and the ultrasonic mixing time is 0.5-2 hours.

3. The preparation method according to claim 1 or 2, characterized in that: The mass ratio of the multi-walled carbon nanotubes modified by MgCl2 to Al in the PATC solution is 10-50%.

4. The preparation method according to claim 1, characterized in that: The inorganic polymer coagulant PATC is prepared by reacting AlCl3 and TiCl4 after being treated in an ice-water bath.

5. The preparation method according to claim 4, characterized in that: The molar ratio of Al in AlCl3 to Ti in TiCl4 is 10-30:

1.

6. The preparation method according to claim 4, characterized in that: The AlCl3 is a 0.05-1.0 mol / L AlCl3 solution, and the TiCl4 is a 98% TiCl4 solution.

7. The preparation method according to claim 4, characterized in that: The reaction solution of AlCl3 and TiCl4 is adjusted to have a basicity of 1.5-1.8 by adding Na2CO3; after stirring for 2-5 hours, it is allowed to stand and mature for 12-24 hours to obtain a PATC solution.

8. The preparation method according to claim 1, characterized in that: The MgCl2-modified multi-walled carbon nanotubes are formed by mixing the multi-walled carbon nanotubes and MgCl2 through oscillation and subjecting them to a pyrolysis reaction at a high temperature of 150-400° C. for 2-5 hours.

9. The preparation method according to claim 8, characterized in that: The shaking time is 12-24 hours.

10. The preparation method according to claim 8, characterized in that: The ratio of the multi-walled carbon nanotubes to MgCl2 is 1g:1-10mmol.

Citation Information

Patent Citations

  • Coagulant for removing humic acid and synthesis method

    CN104261543A

  • Functional magnetic carbon nanotube composite material, preparation method thereof and application of functional magnetic carbon nanotube composite material to water treatment

    CN105797682A

  • Polyaluminum chloride titanium inorganic composite coagulant and preparation method and application thereof

    CN109292936A

  • Preparation method of coagulant for efficiently removing heavy metal Pb2+ in water body

    CN110759445A

  • Method for reducing coal water slurry gasification ash water suspended solids

    CN111302460A